Audit fees and related party transactions: Evidence from Indonesia - Avita Ervianti, Tantri; Supatmi, Supatmi (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2023)
This study empirically examines the impact of related party transactions on audit fees, focusing on distinguishing between tunneling-type and propping-type related party transactions. We investigate this causal relationship by analyzing the influence of various related party transactions on audit fees at the account level, allowing us to pinpoint the specific transactions that exert a more substantial influence on audit costs. Our research sample comprises 127 Indonesian manufacturing firms listed on the Indonesian Stock Exchange during the years 2020-2021, resulting in a dataset of 254 observations. Audit fees are quantified using the natural logarithm of the disclosed annual audit fees. We assess tunneling-type related party transactions by examining the proportion of assets and expenses involved in these transactions, breaking them down into categories such as account receivables, other receivables, and other assets. Similarly, propping-type related party transactions are evaluated based on the proportion of liability-based and sales-based transactions, further disaggregated into account payables, other payables, and other liabilities. Our hypothesis testing relies on a Panel Data Regression analysis model. Our findings reveal that tunneling and propping-type related party transactions significantly increase audit fees. Notably, we demonstrate that tunneling-related party transactions exert a more substantial impact on audit fees than propping-related party transactions, highlighting the significance of agency theory in understanding the risks associated with related party transactions.